Rain reign - Martin, Ann M., 1955- (Feiwel and Friends, 2014)
Struggling with Asperger's, Rose shares a bond with her beloved dog, but when the dog goes missing during a storm, Rose is forced to confront the limits of her comfort levels, even if it means leaving her routines in order to search for her pet.